Tingkat Pengetahuan tentang Vaginal Hygiene Dan Kepuasan terhadap Penggunaan V-Cleanser Foam Berbahan Ekstrak Daun Sirih Hijau - Sukmawati Tansil Tan; Yohanes Firmansyah; Jessica Elizabeth; Jessica Nadia Dinda (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2020)
Many factor affect women’s reproductive health. Vaginal hygiene is important to women because maintaining vaginal hygiene is a part of reproductive health. Women use various feminine hygiene products that often as a part of daily personal cleansing routine. Personal hygiene practices using vaginal hygiene product can affect women’s reproductive health so it is important to have a good level of knowledge about vaginal hygiene to keep a good reproductive health and prevent various kind of reproductive health problems like yeast infetion (candidosis vulvovaginalis) and parasite infection (bacterialis vaginosis) in the future. Some of intimate cleanser product uses natural ingredients, such a reen betel leaf extract which has been studied has antibacterial properties. The aim of the the research is to find out the level of knowledge about vaginal hygiene and the level of satisfaction with the use of V-Cleanser Foam made from green betel leaf extract. This study used descriptive-experimental design with consecutive non random sampling and the data gathered by questionnaire. The respondents of this study were women over 18 years old. From 95 samples, 34,7% of respondents had good level of knowledge, 41,1% had sufficient level of knowledge, and 24,2% had bad level of knowledge about vaginal hygiene. According to the level of satisfaction using the V-cleanser product, the result showed 61% of respondents were very satisfied and 38,9% were satisfied.